A Comprehensive Study of Paadagat Marma with special reference to its Vidha Lakshna (AYUSHDHARA, 2025)
Marma Sharira, a vital aspect of Ayurveda, refers to critical anatomical points that, if injured, can lead to severe consequences or death. According to Sushruta, injuries to Marma points cause imbalances in bodily functions, potentially resulting in death. The study focuses on Marma points in the Paadagat region, including Kurchshira, Kurcha, Talahridaya, and Kshipra, all of which are significant in foot health and can lead to life-threatening conditions. Aim: To study about Paadagat Marma and its Vidha Lakshna. Objectives: 1. To study Paadagat Marma points from ayurvedic texts. 2. To elaborate the anatomical structures related to Paadgat Marma on which an injury can possibly cause Vidha Lakshna as mentioned in Ayurvedic literature. Results: Dissection revealed that each Marma is associated with critical structures: Kurchshira Marma involves tendons and ligaments, while Kurcha Marma is linked to tendons and muscles responsible for foot stability. Talahridaya Marma is situated in the sole and is prone to infections and bleeding, while Kshipra Marma is associated with arterial damage and tetanus. Each injury presents distinct symptoms, such as pain, swelling, tremors, and functional impairment. Discussion: Injuries to these Marma points result in varying degrees of disability and may lead to fatal outcomes if not treated immediately. Kurchshira and Talahridaya are classified as Rujakara and Kalantarapranahara Marma, respectively, while Kurcha and Kshipra are Vaikalyakara Marma due to their impact on foot function and stability. Conclusion: Injuries to Paadagat Marmas require urgent medical intervention due to their potential for severe complications, including death, necessitating quick diagnosis and treatment for effective recovery.